Effects of Scrambling trumpet Creeper flavone on transient cerebral ischemia model (TIA) in rats - Miao, Mingsan (Saudi J Biol Sci, 2018)
To investigate the effects of Scrambling Trumpet Creeper flavone on neurological function score, brain tissue lesion and related biochemical indexes in rat TIA model. Methods: TIA model was induced by tail vein injection of t-butanol (t-BHP). The rats in each administration group were given large, medium and low dose of Scrambling Trumpet Creeper flavone 0.1% CMC suspension, nimodipine and Yangxueqingnao particles group 0.1% CMC suspension, model group and blank group fed the same volume 0.1% CMC. Once a day, continuous administration of 7d. On the 3rd and 6th day after administration, t-BHP was injected into the tail vein, and then placed in a sealed 1 L jar. After 10 min of hypoxia, the neurological function score (NDS) was performed. After the first 2 days of TIA administration, the hem rheology was measured immediately after 1 h of administration, and blood rheology was measured immediately after the administration of blood, blood clotting, hematocrit, hematocrit and whole blood viscosity. After HE is staining to observe the pathological changes of hippocampus and cortex in the left-brain tissue. (LDH) and adenosine triphosphate (ATP) were measured. The right brain tissue of the cerebral cortex was observed. The expression of lactate (LD), lactate dehydrogenase (LDH) Fibroblast growth factor (FGF) and insulin growth factor (IGF) were detected by immunohistochemistry. RESULTS: Compared with the blank group, the coagulation time of the model rats was significantly shortened. The red blood cell deformation index was significantly decreased. Erythrocyte sedimentation rate, hematocrit, plasma viscosity, whole blood viscosity, erythrocyte rigidity index and blood sedimentation equation K value were significantly increased; LD content increased significantly, and LDH, ATP enzyme activity decreased significantly. The positive expression of FGF and IGF in the cortical area had a trend of increasing. CONCLUSION: The Scrambling Trumpet Creeper flavone significantly improved the indexes of whole blood rheology; the energy metabolism of cerebral ischemia was increased, and the positive expression of neurotrophic factor in cortex was significantly increased.